Ethical Challenges of Using Artificial Intelligence in Higher Education Organizations (Journal of Universal Excellence, 2026)
Research Question (RQ): What are the key ethical challenges and dilemmas associated with the use of conversational chatbots like ChatGPT in higher education? What guidelines do instructors and universities recommend for the fair, ethical, and transparent integration of AI as an educational tool?Purpose: To identify key ethical challenges and dilemmas related to the use of AI tools based on large language models (e.g., ChatGPT); to propose guidelines for the ethical and responsible use of these technologies in an academic setting; to contribute to the discourse on AI ethics in education and highlight the need for further research in this area.Method: This article is theoretical in nature and is based on a review of existing literature and sources on the topic of AI ethics in education.Results: The research identifies multifaceted ethical challenges associated with artificial intelligence, such as issues of transparency, privacy, data ownership, academic integrity, and long-term consequences on the quality of learning. Specific guidelines are proposed for the ethical use of AI in pedagogical and research purposes at the university level. The need for training of teachers and students as well as further research in this field is emphasized.Organization: The study sheds light on significant ethical challenges that higher education institutions face when integrating AI tools into the pedagogical process. The proposed guidelines can assist managers in shaping institutional policies for the ethical and responsible use of these technologies. It contributes to considerations regarding the long-term effects of AI on the quality of teaching and learning.Society: This contribution initiates an important societal discussion on AI ethics in education. It encourages contemplation about the societal consequences of such technologies and raises awareness about the importance of transparency, data privacy, and equal access. It can influence the formulation of public policies in this domain.Originality: The article comprehensively addresses ethical dilemmas of AI in the pedagogical context. The proposed guidelines can assist educational institutions in shaping their own policies for the ethical use of these technologies. It contributes to the synthesis of existing knowledge and practical implications.Limitations/Future Research: Since this is an evolving phenomenon, further research on the actual effects and experiences of using AI in practice is necessary.